Widespread anti‐sense transcription in apple is correlated with siRNA production and indicates a large potential for transcriptional and/or post‐transcriptional control. Issue 1 (1st April 2014) - Celton, Jean‐Marc; Gaillard, Sylvain; Bruneau, Maryline; Pelletier, Sandra; Aubourg, Sébastien; Martin‐Magniette, Marie‐Laure; Navarro, Lionel; Laurens, François; Renou, Jean‐Pierre
Summary: Characterizing the transcriptome of eukaryotic organisms is essential for studying gene regulation and its impact on phenotype. The realization that anti‐sense (AS) and noncoding RNA transcription is pervasive in many genomes has emphasized our limited understanding of gene transcription and post‐transcriptional regulation. Numerous mechanisms including convergent transcription, anti‐correlated expression of sense and AS transcripts, and RNAi remain ill‐defined. Here, we have combined microarray analysis and high‐throughput sequencing of small RNAs (sRNAs) to unravel the complexity of transcriptional and potential post‐transcriptional regulation in eight organs of apple ( Malus × domestica ). The percentage of AS transcript expression is higher than that identified in annual plants such as rice and Arabidopsis thaliana . Furthermore, we show that a majority of AS transcripts are transcribed beyond 3′UTR regions, and may cover a significant portion of the predicted sense transcripts. Finally we demonstrate at a genome‐wide scale that anti‐sense transcript expression is correlated with the presence of both short (21–23 nt) and long (> 30 nt) siRNAs, and that the sRNA coverage depth varies with the level of AS transcript expression. Our study provides a new insight on the functional role of anti‐sense transcripts at the genome‐wide level, and a new basis for the understanding of sRNA biogenesis in plants.